Activation of Functional Somatic Stem Cells Promotes Endogenous Tissue Regeneration. (July 2022) - Li, W.; Huang, X.; Yu, W.; Xu, Y.; Huang, R.; Park, J.; Moshaverinia, A.; Arora, P.; Chen, C.
Periodontal ligament derived stem cells (PDLSCs) are capable of differentiating into multiple cell types and inducing a promising immunomodulation for tissue regeneration and disease treatment. However, it is still challenging to develop a practical approach to activate endogenous stem cells for tissue self-healing and regeneration. In this study, transcriptome analysis reveals that resveratrol promotes PDLSC stemness through activation of stem cell, osteoprogenitor, and chondroprogenitor markers. Self-renewal and multipotent differentiation abilities are also improved in resveratrol-treated PDLSCs. In addition, immunomodulation of PDLSCs is dramatically increased after resveratrol treatment. Mechanistically, we show that resveratrol activates ERK/WNT crosstalk through elevation of olfactory and growth factor signaling pathways to upregulate the expression levels of RUNX2 and FASL for osteogenesis and immunomodulation, respectively. By using a periodontitis animal model, administration of resveratrol partially rescues bone loss through activation of endogenous somatic stem cells and inhibition of inflammatory T-cell infiltration. Taken together, our findings identify a novel pharmacological approach to achieve autotherapies for endogenous tissue regeneration.